Atividade investigativa sobre nutrientes dos alimentos: possíveis contribuições da teoria da aprendizagem significativa - Zômpero, Andreia Freitas; Sampaio, Helenara Regina; Laburú, Carlos Eduardo; Gonçalves, Carlos Souza (Góndola, enseñanza y aprendizaje de las ciencias, 2014)
The study presents the analysis of a research activity about food and its nutrients applied in the discipline of science elementary school in a public school in the city of Londrina (Brazil), based on the Theory of Significant learning. The objective of the research was to determine the relationship between the development of a research activity with the use of nutritional tables, and aspects related to the theory of meaningful learning. Through the analysis it was possible to establish relationships between features investigative proposed by the National Research Council, such as student engagement, prioritization and explanations of the evidence through student records, connecting explanations to scientific knowledge and communication with aspects the theory of meaningful learning.